Comparison of digital audio watermarking techniques for the security of VOIP communications - (:unkn) unknown (My University, 2011)
In this paper, the authors present digital audio watermarking techniques that can be used for source origin authentication in real-time Session Initiation Protocol (SIP) Communications, such as Voice over IP (VoIP). The watermark-enabled VoIP mechanism utilizes audio watermarking techniques as a covert channel between calling parties to send source origin indicator information during the transportation phase of VoIP. The effects of audio watermarking were measured using the Signal-to-Noise Ratio, watermark extract durations and the effects of a-law, u-law and GSM encoding during the transportation phase of VoIP. Moreover, various audio watermarking algorithms were implemented to demonstrate the applicability of aforementioned security solution in terms of certain parameters: robustness, evaluation times, complexity and capacity. The experimental results suggest that some watermarking algorithms are applicable in VoIP, while others are not suitable for source origin authentication. © 2011 IEEE.
Keywords: Audio Codecs; Audio Watermarking; Session Initiation Protocol; VoIP Authentication